2021
DOI: 10.4236/ce.2021.126092
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Rapid Transition to Online Teaching during COVID 19: An Online Cross-Sectional Survey of Students’ and Teachers’ Perceptions in a West Indian Dental School

Abstract: Objectives: The sudden advent of the COVID pandemic resulted in limited face to face interactions and the dental school in the University of the West Indies was challenged to complete the final year with a rapid transition to online teaching. This study examined students' and teachers' perceptions of the effectiveness of emergency remote online teaching and challenges experienced. Materials and Methods: Two independent online cross-sectional surveys were administered on the perception of the online learning en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
1
3
1
Order By: Relevance
“…Both, male and female students acknowledged their teachers' support, availability and timely feedback, which was in line with other studies that also showed an appreciation of the support provided by teachers during distance learning (Rafeek et al, 2021;Li et al, 2021;Aristovnik et al, 2020). As timely feedback has been emphasized as important contributor for the advancement of one's work this is a critical component to successful teaching and learning (Ozfidan et al, 2021).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Both, male and female students acknowledged their teachers' support, availability and timely feedback, which was in line with other studies that also showed an appreciation of the support provided by teachers during distance learning (Rafeek et al, 2021;Li et al, 2021;Aristovnik et al, 2020). As timely feedback has been emphasized as important contributor for the advancement of one's work this is a critical component to successful teaching and learning (Ozfidan et al, 2021).…”
Section: Discussionsupporting
confidence: 85%
“…A lack of social contacts can also very easily lead to a higher perception of loneliness or social isolation and psychological stress (Zhou et al, 2020). According to international studies, women are more affected by this problem than men and, therefore, may require additional attention (Tavolacci et al, 2013;Holt-Lunstad, 2017;Liu et al, 2019;Luo et al, 2020;Atienza-Carbonell & Balanzá-Martínez, 2020) In contrast to previous studies (Rafeek et al, 2021;Khraishi, 2021;Ntim et al, 2021) almost two-thirds of students in the present study considered digital education not as essential or helpful for their studies and knowledge transfer at the university level. Both, male and female students emphasized that certain course contents could not be sufficiently transferred into a digital format.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…When we combined the extremely ineffective and ineffective category into an ineffective category, 66(80.5%) of the respondents confirmed that VL is ineffective for clinical skill and 72(87.8%) reported it was ineffective for building the social skill as well which is similar with the result of the study conducted in West Indian dental school. 16 while the opposite is true for class room learning. A total of 68(83%) respondents accepted that class room learning is either extremely effective or effective for enhancing clinical as well as social skill.…”
Section: Discussionmentioning
confidence: 97%
“…Many studies related to the psychological state of adolescent students have been cited in the literature (Zhai & Du, 2020;Oza et al, 2022;Pellino et al, 2021;Rafeek et al, 2021). These studies have highlighted many causes and factors that affected the psychological state of students and their repercussions on their academic results.…”
Section: Related Workmentioning
confidence: 99%